Menerima Karunia Selibat: Karunia yang Khas dari Allah (Eksegesa 1 Korintus 7:7) - Kezia Hutagalung (Sekolah Tinggi Theologia Nazarene Indonesia, 2019)
Paul as the founder of the Corinthians church, he wrote this letter when he was in Ephesians. Specially in this part, Paul answered the questions from them about someone should get merried or not, that is depend their gift from God. Related to the Corinthians life, they are still affected by the dirtiness, also with the assumption of some congregations that it is better not to mary so they can live according to the gospel.